Native ruminants improve productivity - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Indigenous sheep and goats Mozambique and Rwanda which are adapted to the stresses of the African environment, could help increase the reproductive performance of small ruminants in semi-arid regions throughout Africa. Two breed characterisation...